ANGGARAN CUPET PEMBANGUNAN MACET - Florentinus Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2017)
The aim of this research is to know about the budget of Samarinda  Local Government. The forms of the budget of the organization has the characteristics as follow ,(1).It is stated in the unity of monitory by the supporting nonmoneter like production unit or sold unit ,(2).To cover the defined period usually one year,(3).To estimate the potencial profit of the bisness unit ,(4). As the commitment ,(5).The  udget being reviewed and agreed ,(6). After it is being appointed so never change again withou the special reason.The location of it is in Samarinda in 2016.The method of the research is qualitative  by taking from newspaper ,magazine and reports.The data is also taken by observation and interview.The  budget here was falling down until 2 tryllion rupiah .The results are  that (1).The budget falling down until Rp. 2 Trylion ,(2).The budget is just the rest namely Rp 2632,79 milyard .The suggestions are that the government, (1). has to cut the budget of the expense ,(2).has to economize the budget , (3).To increase the real income by tax.